Simulation of Forced Convection in a Pipe with Nano Fluids Using Ansys CFX Software - Pushparaj , M.; Anand Vino, Jose (International Journal of Psychosocial Rehabilitation, 2019)
Conventional fluids such as water and ethylene glycol are normally used as heat transfer fluids. Various techniques are applied to enhance the heat transfer. The low heat transfer performance of these conventional fluids obstructs the performance enhancement. The use of additives is a technique applied to enhance the heat transfer performance of base fluids. Recently, as in conventional heat nanofluids. The suspended metallic or nonmetallic nanoparticles change the transport properties and heat transfer characteristics of the base fluid. In this project, we have considered the problem of forced convection flow of fluid inside a uniformly heated tube that is subjected to a constant and uniform heat flux at the wall. The heat transfer coefficient we analyzed at the same Reynolds number for both base fluids and nanofluids in the CFX software. The base fluids used for this work are water and ethylene glycol. The nano particles to suspended in the base fluids used for this work are aluminum, aluminum oxide, copper, copper oxide and silver